The Effect of the E-Module-Assisted Guided Inquiry Model through Student Learning Outcomes in Substance Pressure Material - Rafiqa Nurhidayah Hasibuan; Ridwan Abdullah Sani (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
This research aims to analyze the influence and increase in student learning outcomes using the guided inquiry model assisted by e-modules through the Professional Flip PDF application on substance pressure material. The research used a quasi-experimental method with a two-group pretest-posttest design. The sampling technique uses random cluster sampling. The research sample consisted of two classes, namely the VIII-4 experimental class with 31 students and the control class VIII-2 with 29 students. The research instrument uses a learning outcomes test instrument with 20 multiple-choice questions. The results of the pretest mean value of the experimental class were 47.41 with a standard deviation of 9.02, and the average value of the control class was 41.03 with a standard deviation of 8.80. The results of learning through hypothesis testing obtained tcount> ttable (6.59 <1671) so that Ha is accepted and rejects Ho. In conclusion, there is an influence of the assisted guided inquiry model e-module on student learning outcomes on material pressure material.